The Political Education Strategy of the Golkar Party for Constituents: Challenges and Its Impact on Local Political Participation - Sabir, Arisman; Murni, Yanti; Afrianti, Rini; Mufti, Dhini; Yanti, Fitri; Fauziah (Yayasan Ilomata, 2025)
This research aims to analyze the role of the Golkar Party in providing political education to its constituents. Political education is an essential part of democracy development, enabling society to understand their rights and responsibilities in the political process. Through various programs and activities, the Golkar Party seeks to enhance political awareness among the public and build an understanding of the political system, public policies, and the electoral process. This study employs a qualitative approach with a case study method in several areas where the Golkar Party has a strong support base. Data were collected through interviews, observations, and document studies. The findings indicate that the political education conducted by the Golkar Party plays a crucial role in increasing political participation among constituents, although there are challenges regarding the effectiveness and consistency of the programs. This research provides insights into the strategies used by political parties to influence public political understanding and its implications for local political dynamics.